Transforming Higher Education: A Multicultural Curriculum Framework to Promote Religious Moderation in Indonesia - Arikah Izzah; Wiwin Fachrudin Yusuf (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2026)
This research aims to explore the role of multicultural education, active campus participation, and challenges in implementing moderation and tolerance in higher education. In an increasingly diverse society, universities play a pivotal role in promoting religious moderation and tolerance among students. However, despite these efforts, various challenges hinder their successful implementation. This study employs a qualitative approach, utilizing interviews with faculty and students, along with observational data, to analyze the integration of multicultural education and its impact on students' attitudes towards tolerance. The research identifies three key findings: (1) multicultural education fosters religious moderation through both theoretical learning and practical experiences; (2) active participation in campus activities such as interfaith dialogues and cultural workshops enhances students' understanding and appreciation of diversity; (3) external factors like social media and initial student resistance pose significant challenges to the development of moderation. The study contributes to the body of knowledge on multicultural education in higher education and recommends that universities adopt more inclusive policies and encourage broader student involvement in multicultural activities. Future research should expand on these findings by examining the impact of media and external societal influences.